Odpowiedzi

2010-03-22T16:09:41+01:00
A 2*(-4) +1=-7
b 2*0+1=1
c 2*1 1/2 +1=4


a
5-3*(-2)=-1
5-3*0,4=3,8
1 2 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-22T16:11:41+01:00
A)2*-(4)+1=8+1=9
b)2*0+1=01=1
c)2*1 1/2+1=3+1=4
d)2*2/3+1=1 1/3+1=2 1/3

a)5-3*(-2)=5-(-6)=11
b)5-3*0.4=5-1.2=3.8
liczę na naj
2010-03-22T16:12:08+01:00
2x+1
a)2 × (-4) +1= 8+1=9
b)2 x 0 +1 = 0+1=1
c)2 x 1½ + 1 = 2 x 3/2 + 1 =3+1=4
d)2 x ⅔ + 1 = 4/3 + 1 = 1 ⅓ + 1 = 2 ⅓


5-3x
5 - 3 x (-2) = 5+6=11
5 - 3 x (0,4) = 5 - 1,2 = 3,8